PENGARUH PEMBERIAN POLIFENOL DARI TANAMAN HERBAL SEBAGAI NATURAL FEED ADDITIVE TERHADAP PERFORMA ANAK KAMBING DAN DOMBA - Endah Yuniarti; Raden Febrianto Christi; Ken Ratu Gharizah Alhuur (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
The antibiotics as feed additive had been prohibited by the government regulation, because it was feared that it would pose a risk to livestock and residues in the products they produce. The ban is an opportunity for the development of innovations in feeding, such as the use of herbal plants as natural feed additives (NFA). The provision of NFA had been carried out by several researchers to the performance of kids and lambs. Kids and lambs are one of the key stages of successful sheep and goat farming. Kids and lambs that are healthy and have good performance will certainly be good breeds for livestock farming. Utilization of herbs and spices containing polyphenolic compounds has various effects on livestock, especially kids and lambs. The benefits or effects of NFA on kids and lambs are summarized in several studies, namely faster livestock growth, increased feed digestibility, feed efficiency, and economic efficiency. In addition, NFA also affects metabolic function and immunity, and reduces methane gas emissions without disturbing the rumen microbial population. Meat produced from kids and lambs supplemented with NFA also showed increased oxidative stability and increased PUFA and MUFA levels. Keywords: additive, herb, polyphenol, goat, lamb, kids